2020
DOI: 10.1101/2020.08.19.258509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient 5-OP-RU-induced enrichment of Mucosal-associated invariant T cells in the murine lung does not enhance control of aerosolMycobacterium tuberculosisinfection

Abstract: Mucosal-associated invariant T (MAIT) cells are an innate-like T cell subset in mammals that recognize microbial vitamin B metabolites presented by the evolutionarily conserved MHC I-related molecule MR1. Emerging data suggest that MAIT cells may be an attractive target for vaccine-induced protection against bacterial infections because of their rapid cytotoxic responses at mucosal services to a widely conserved bacterial ligand. In this study, we tested whether a MAIT cell priming strategy could protect again… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…It remains unclear, however, whether maintained MAIT cell function would contribute to the overall immune response against Mtb . Although MAIT cells in humans are enriched in the lungs during TB infection and are more pro-inflammatory than their peripheral blood counterparts ( 4 , 8 ), recent evidence in the murine and non-human primate models suggests they may not contribute to protection against Mtb ( 11 13 ). Further work is required to elucidate the role of bronchoalveolar and lung-resident MAIT cells in the human immune response to Mtb .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear, however, whether maintained MAIT cell function would contribute to the overall immune response against Mtb . Although MAIT cells in humans are enriched in the lungs during TB infection and are more pro-inflammatory than their peripheral blood counterparts ( 4 , 8 ), recent evidence in the murine and non-human primate models suggests they may not contribute to protection against Mtb ( 11 13 ). Further work is required to elucidate the role of bronchoalveolar and lung-resident MAIT cells in the human immune response to Mtb .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MAIT cells make up a large proportion of Mtb -reactive CD8+ T cells in the peripheral blood of humans, suggesting their potential importance in anti-TB immunity ( 4 , 10 ). Nonetheless, the specific role of MAIT cells in protection against human respiratory infections, including TB, remains unclear ( 11 13 ). MAIT cells are also able to respond to viral infection, the recognition of which is mediated by IL-18 and IL-12 stimulation ( 14 , 15 ) rather than by ligand-driven T cell receptor mediated response.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that lung infection of MR1 −/− mice was more serious after 10 days of infection compared with the control group, while there was no significant difference in bacterial load between the two groups after 30 days of infection [67] . Another study has shown that intranasal co-stimulation of mice with lipopeptide TLR agonist and synthetic MR1 ligand induces early MAIT cell activation and expansion after M. tuberculosis exposure, while MAIT cells are not sufficient to control M. tuberculosis bacterial load [5] . MAIT cells produce IL-17, which may help to stimulate an adaptive immune response.…”
Section: Mait Cells In Lung Diseasesmentioning
confidence: 99%
“…These innate T cells are unconventional T cells share the same characteristics as innate and adaptive immunity, recognizing antigens through T cell receptors (TCRs) and being stimulated by cytokines directly [3] . Over the past few decades, the development of gene-targeted mice and tetramers has increased interest in the function and role of unconventional T cells in tissue homeostasis and disease [4] , [5] , [6] . There is increasing evidence to indicate that MAIT cells quickly recognize microbial metabolites antigenic ligands presented by conserved MHC-I-related molecule MR1 [7] , they have an important role in innate immunity to pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that MAIT cells make up a large proportion of Mtb -reactive CD8+ T cells in the peripheral blood of humans, suggesting their potential importance in anti-TB immunity [3, 9]. Nonetheless, the specific role of MAIT cells in protection against human respiratory infections, including TB, remains unclear [1012]. MAIT cells are also able to respond to viral infection, the recognition of which is mediated by IL-18 and IL-12 stimulation [13, 14] rather than by ligand-driven T cell receptor mediated response.…”
Section: Introductionmentioning
confidence: 99%